URGENSI PEMBUKTIAN REKAM MEDIS ELEKTRONIK DALAM PERSPEKTIF HUKUM DI INDONESIA - Engga Lift Irwanto; Yussy Adelina Mannas; Syofirman Syofyan (LPPM Universitas Ekasakti Padang, 2023)
The development of science also has a significant impact on the development of good health service provision. One of the developments in the field of health services is the renewal of electronic medical records. Where the benefits of electronic medical records are of course as a basis or guide to knowing and analyzing diseases and knowing the treatment, care and medical action that must be given to patients, as well as improving the quality of service to protect medical personnel in the promotion of optimal public health. Then this electronic medical record can also be used as a type of evidence to be able to make light of a certain legal event. The medical legal basis for electronic records is evidence based on Law Number 29 of 2004 concerning Medical Practice and Law Number 11 of 2008 concerning Information and Electronic Transactions. Then this research is a normative research or library research that will examine the urgency of proving electronic medical records based on a legal perspective in Indonesia.